2016
DOI: 10.1590/1678-98652016000200001
|View full text |Cite
|
Sign up to set email alerts
|

Social and demographic inequalities in diet quality in a population-based study

Abstract: A B S T R A C T ObjectiveTo evaluate sociodemographic inequalities in the diet quality of the urban population of the city of Campinas, São Paulo, Brazil. MethodsA population-based, cross-sectional study was performed using data from a health survey conducted in the city of Campinas in 2008-2009. Diet quality was evaluated using the Brazilian Healthy Eating Index Revised. A total of 3,382 individuals aged 10 years old and older were analyzed. ResultsBrazilian Healthy Eating Index Revised scores increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 36 publications
4
19
1
5
Order By: Relevance
“…Among these, Wendap et al [43] obtained a mean BHEI-R score higher than that of this research (75.1 points), while Previdelli et al [10] found a lower mean (47.1 points). In a population-based study, the mean BHEI-R of adolescents was closer to that of this research (52.4 points) [46]. Considering the maximum BHEI-R score of 100 points, the diet quality of the respondents was unsatisfactory.…”
Section: Discussionsupporting
confidence: 46%
“…Among these, Wendap et al [43] obtained a mean BHEI-R score higher than that of this research (75.1 points), while Previdelli et al [10] found a lower mean (47.1 points). In a population-based study, the mean BHEI-R of adolescents was closer to that of this research (52.4 points) [46]. Considering the maximum BHEI-R score of 100 points, the diet quality of the respondents was unsatisfactory.…”
Section: Discussionsupporting
confidence: 46%
“…However, some studies with adults and older adults have reported higher BHEI score for women [9,10]. Assumpção et al [10] found that women consumed more vegetables, fruits, and milk and less sodium, meat, saturated fat, alcohol, and added sugar, when compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies with adults and older adults have reported higher BHEI score for women [9,10]. Assumpção et al [10] found that women consumed more vegetables, fruits, and milk and less sodium, meat, saturated fat, alcohol, and added sugar, when compared to men. The diet quality similarity found between female and male individuals living in São Caetano do Sul can be explained by the fact that most of the older adults studied were married and retired, and thus they probably had meals together with their spouses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations